2018
DOI: 10.33549/physiolres.933467
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Spexin and Kisspeptin Negatively Correlate With Obesity and Insulin Resistance in Women

Abstract: Spexin (SPX) and kisspeptin (KISS) are novel peptides relevant in the context of regulation of metabolism, food intake, puberty and reproduction. Here, we studied changes of serum SPX and KISS levels in female non-obese volunteers (BMI<25 kg/m2) and obese patients (BMI>35 kg/m2). Correlations between SPX or KISS with BMI, McAuley index, QUICKI, HOMA IR, serum levels of insulin, glucagon, leptin, adiponectin, orexin-A, obestatin, ghrelin and GLP-1 were assessed. Obese patients had lower SPX and KISS level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
84
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 50 publications
7
84
3
Order By: Relevance
“…Higher KP in nonobese males and nonobese young females was observed in our study, which might be due to the fact that KP affects negatively on body weight and calorie consumption (Walewski et al, #216). BMI and body fat % age were noted to be high in infertile groups while KP was low which is perhaps due to certain changes in the sex hormones which regulates obesity by increasing the serum triglycerides levels (Kołodziejski et al, ; Shamai et al, ). It is a well‐established fact that there are various mechanisms how obesity causes infertility (Talmor & Dunphy, ).…”
Section: Discussionmentioning
confidence: 99%
“…Higher KP in nonobese males and nonobese young females was observed in our study, which might be due to the fact that KP affects negatively on body weight and calorie consumption (Walewski et al, #216). BMI and body fat % age were noted to be high in infertile groups while KP was low which is perhaps due to certain changes in the sex hormones which regulates obesity by increasing the serum triglycerides levels (Kołodziejski et al, ; Shamai et al, ). It is a well‐established fact that there are various mechanisms how obesity causes infertility (Talmor & Dunphy, ).…”
Section: Discussionmentioning
confidence: 99%
“…Obese individuals were found to have lower serum kisspeptin levels compared with normoweight individuals (30). Furthermore, there is an inverse association between serum kisspeptin levels and BMI, but a positive correlation between kisspeptin and serum adiponectin levels (30). This correlation was further supported by Zhou et al (37), who demonstrated that high-fat diet-induced obesity caused a marked suppression of ovarian Kiss1 mRNA levels in mice at postnatal days 42 and 70 compared with normoweight mice on normal chow diet.…”
Section: Discussionmentioning
confidence: 85%
“…These findings indicate that certain related metabolic disorders, such as obesity and diabetes mellitus, are involved in the regulation of kisspeptin through hormones such as adiponectin. Obese individuals were found to have lower serum kisspeptin levels compared with normoweight individuals (30). Furthermore, there is an inverse association between serum kisspeptin levels and BMI, but a positive correlation between kisspeptin and serum adiponectin levels (30).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations